2016
DOI: 10.3329/bjsir.v51i2.28098
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrics, length-weight relationship and ecological factors affecting the habitat of Pila globosa (Swainson, 1822) (Mesogastropoda: Pilidae) located in Rajshahi University campus

Abstract: The investigation was conducted on morphometrics, length-weight relationship and ecological factors of the freshwater apple snail, Pila globosa (Swainson, 1822) in the habitat of Rajshahi University Campus. The length of shell (SL) (40.09 ± 16.08 mm), length of spire (SPL) (7.63 ± 2.61mm), length of base (LB) (32.52 ± 13.58 mm), width of shell (SW) (37.39 ± 15.72 mm), length of aperture (AL) (27.83 ± 10.42mm) and width of aperture (AW) (16.6 ± 6.46mm) in combined sex were observed. The obesity indices of male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Seasonal length-weight relationships indicated that the exponent value for both sexes is quite high during the monsoon, which may be due to more suitable environmental conditions and better availability of favourable food items for growth and maturation of gonads. Overall exponent value for pooled data indicated that the species has negative allometric growth, which agrees with the earlier report on P. globosa from Bangladesh waters (Saha et al, 2016). The relative condition factor values for all the specimens ranged from 0.84 to 1.21, with an average of 1.01 and a maximum Kn value was obtained for males (1.07).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Seasonal length-weight relationships indicated that the exponent value for both sexes is quite high during the monsoon, which may be due to more suitable environmental conditions and better availability of favourable food items for growth and maturation of gonads. Overall exponent value for pooled data indicated that the species has negative allometric growth, which agrees with the earlier report on P. globosa from Bangladesh waters (Saha et al, 2016). The relative condition factor values for all the specimens ranged from 0.84 to 1.21, with an average of 1.01 and a maximum Kn value was obtained for males (1.07).…”
Section: Discussionsupporting
confidence: 89%
“…It is also used as an animal feed additive in freshwater aquaculture in this region due to the high protein content of their meat. Some studies have been carried out earlier on its length-frequency distribution, morphometry, length-weight relationship and condition factor from India and adjacent countries (Saha et al, 2016;Panda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%